2023
DOI: 10.1039/d2nh00557c
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the room temperature growth of two-dimensional h-BN nanosheets for multifunctional applications

Abstract: Room temperature growth of two-dimensional van der Waals (2D-vdW) materials is indispensable for state-of-the-art nanotechnology as it supersedes the requirement of elevated growth temperature accompanied with additional high thermal budgets,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…Figure presents the static and dynamic WCA of freshly exfoliated hBN samples. The static WCA value was found to be 64 ± 5°, which is consistent with some previous reports. ,, The advancing WCA was found to be 79 ± 3°, while the receding WCA was found to be 43 ± 4°. It is worth noting that no prior research reported experimental values of advancing and receding WCAs of freshly exfoliated hBN, likely due to the very small size and hBN crystal available …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure presents the static and dynamic WCA of freshly exfoliated hBN samples. The static WCA value was found to be 64 ± 5°, which is consistent with some previous reports. ,, The advancing WCA was found to be 79 ± 3°, while the receding WCA was found to be 43 ± 4°. It is worth noting that no prior research reported experimental values of advancing and receding WCAs of freshly exfoliated hBN, likely due to the very small size and hBN crystal available …”
Section: Resultsmentioning
confidence: 99%
“…Numerous techniques, for the preparation of graphene, have been used to date to synthesize hBN nanosheets, ,, including exfoliation methods from bulk materials (e.g., mechanical, chemical, thermal, etc. ), intercalation approaches, solid and liquid phase sonification methods, mechanical milling techniques, chemical solution derived (CSD) techniques, CVD, and PLD. ,,,, It is important to note that the synthesis of high-quality hBN is still very challenging and the quality of the resulting nanosheets is yet to be improved. The bulk hBN crystals produced thus far have exhibited lower quality and smaller dimensions in comparison to those of highly ordered pyrolytic graphite (HOPG).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, two-dimensional materials, such as MOX [13,14], TMDs [15,16], h-BN [17,18], MXenes [19,20] are widely studied. Among them, two-dimensional transition metal carbon/nitride (MXenes) materials are excellent candidates for device applications due to their excellent stability, electrical conductivity and capacitance [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%